Analisis Studi Kelayakan Usaha Home Industry Pengolahan dan Pengemasan Tahu pada UD Djawa Mandiri - Sri Kalimah; Umi Nadhiroh; Rosyidatul Malikah (STATERA: Jurnal Akuntansi dan Keuangan, 2019)
A business feasibility study is indispensable for predicting a picture of being worthy or not like a business to run, the research aims to be able to see if the Home industry processing and packaging know UD. Djawa Mandiri. As souvenirs typical of Kediri deserve to be executed or not. Assessment is not only done in one aspect alone but every aspect to say worthy should have a certain standard of value, however. The methods of analysis used in business feasibility studies include the aspect of market potential and marketing, aspects of management/organizational, aspects of human resources, technical and technological aspects, and financial aspects that include Payback Period (PP), Average rate of Return (ARR), Net Present Value (NPV), and Profitability Index (PI). The results of this study were obtained that UD Djawa Mandiri business deserves to run and have a very good prospect.